Jurisprudence and its controls : A Comparative study - Abdulhakeem, Zeena; Fleh, Haider (Journal of Legal Sciences, 2022)
Judicial jurisprudence is one of the important legal solutions to address the shortcomings of legislation. Throughout its long history, human societies have known many cases in which the judge finds himself facing a legislative vacuum in addition to civil legal texts that are difficult for the judge to implement due to ambiguity or contradiction, which requires diligence. To rule on resolving disputes before him in order not to deny justice, but the judge in his jurisprudence was not absolute, but rather bound by certain controls represented by observing the wisdom of legislation on the one hand and taking into account the nature of the texts on the other side, and from here this research came to shed light on the jurisprudence and its controls ...We have reached a set of recommendations, the most important of which is the need to amend Articles (1) and (2) of the Iraqi Civil Code, as well as a set of recommendations that we have mentioned in the course of the research, which we hope the legislator and judges will pay attention to.